2008
DOI: 10.1021/jp8008628
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Investigation of the Decomposition of Lithiated Hydroxyl Side-Chain Amino Acids

Abstract: Lithium cation complexes with serine (Ser) and threonine (Thr) are collisionally activated with xenon in a guided ion beam tandem mass spectrometer and are observed to exhibit a variety of decomposition pathways in addition to a loss of the intact ligand. Prominent pathways include a loss of H2O, CO2, and aldehydes (XCHO where X=H for Ser and CH3 for Thr). Quantum chemical calculations at the B3LYP/6-311+G(d,p) level are used to explore the reaction mechanisms for these processes in detail. Complete potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
35
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 34 publications
13
35
0
Order By: Relevance
“…As noted above, the competitive shift observed in the Li + (Pro) system is about 0.14 eV, consistent with previous results for similarly sized systems [43,44]. In the case of Li + (NMP), analysis of the Li + cross section with and without including competition with CO loss gives the same threshold energy of ∼3.4 eV, but utilizes very different n values.…”
Section: Threshold Analysis For LI + (Nmp)supporting
confidence: 89%
See 3 more Smart Citations
“…As noted above, the competitive shift observed in the Li + (Pro) system is about 0.14 eV, consistent with previous results for similarly sized systems [43,44]. In the case of Li + (NMP), analysis of the Li + cross section with and without including competition with CO loss gives the same threshold energy of ∼3.4 eV, but utilizes very different n values.…”
Section: Threshold Analysis For LI + (Nmp)supporting
confidence: 89%
“…This difference is in agreement with the previous study [5] and with theory, which predicts an increase of 8-15 kJ/mol. This increase in the Li + binding energy upon methylation also agrees with increases measured for similar methylated systems studied previously [5,44,[51][52][53].…”
Section: Side-chain Effectssupporting
confidence: 89%
See 2 more Smart Citations
“…Alternatively, CO 2 elimination could occur first, leading to complex III, where the metal is coordinated to the side chain and contains an M─C bond, reminiscent of the mechanism proposed by Ye and Armentrout for the loss of CO 2 from lithium complexes with serine and threonine [48]. , it was previously reported that the 61 Da loss could also involve H 2 O and HNCO [17].…”
Section: Loss Of (Nh 3 + Co 2 )mentioning
confidence: 94%